ANALISIS KINERJA SEKRETARIS DESA PADA KECAMATAN TOLITOLI UTARA KABUPATEN TOLITOLI - Syah Fithrah, Mohammad (Katalogis, 2015)
This research is conducted to determine the performance of Village Secretary at Sub District Northern Tolitoli of District Tolitoli. Type of research is qualitative. Selected samples are 3 villages, namely village Teluk jaya, Laulalang, and village Lakuan, Tolitoli. There are seven iformants in this research. Data collection techniques are observation, interviews, and documentation. Data analysis techniques are data reduction, data organization, data interpretation and conclusions. This research uses Robbins’ performance theory seen of aspect of the Knowledge, Skills, and Motivation. Research result shows that the performance of Village Secretary of sub-district Northern reviewed on indicators of Knowledge, Skills and Motivation, is still not optimal, for knowledge indicator it is due to the lack of guidance to the village secretary also low education level affects the ability in implementing the main tasks and functions as administrators in the village administration, to see the result of skills indicator or the village secretary skill, it is also not maximized due to the influence of the secretary knowledge in applying the skills capabilities, interacting and utilizing the facilities and infrastructure supporting administrative services in the village, while the motivation indicator is not optimal due to the minimum facilities and infrastructure supporting the performance of the village secretary at Sub-district Northern Tolitoli of District Tolitoli.